Doing statistical analysis : a student's guide to quantitative research - Thrane, Christer (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Doing Statistical Analysis looks at three kinds of statistical research questions - descriptive, associational and inferential - and shows students how to conduct statistical analyses and interpret the results. Keeping equations to a minimum, it uses a conversational style and relatable examples such as football, covid-19 and tourism, to aid understanding. Each chapter contains practice exercises, and a section showing students how to reproduce the statistical results in the book using Stata and SPSS. Digital supplements consist of data sets in Stata, SPSS and Excel, practical videos explaining how to do basic analysis, and a test bank for instructors. Its accessible approach means this is the ideal textbook for undergraduate students across the social and behavioural sciences needing to build their confidence with statistical analysis"--
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Statistical methods; Research -- Statistical methods